THE EFFECT OF CUSTOMER EXPERIENCE DESIGN, RELATIONSHIP QUALITY, AND EMOTION CONNECTION ON LOYALTY - Elia Ardyan (Journal of Management and Business, 2014)
The purpose of this study is to determine the effect of customer experience design, emotion connection and relationship quality on customer loyalty. Hotel must manage the consumer experience well. When the consumer experience increase, it will give effect to increasing relationships quality and emotional connection. Increasing the quality of the relationship and emotional connection between the consumer and hotel is expected to increase customer loyalty. The sample in this study is 142 respondents. The analysis in this study uses a structural equation model, in which we use Amos version 20 to help data analysis. The result of this study : (1) there are positive and significant effects between customer experience design on relationship quality and between customer experience on emotional connection; (2) there are not any positive and significant effects between customer experience design, emotional connection, and relationship quality on custimer loyalty.